Strategies to Build Customer Trust Based on Service Quality and Relationship Quality: Anchorage Study in Riau Islands - Rosita Septiani; Syafriza Syafrizal (Jurnal Indonesia Sosial Teknologi, 2024)
This study examines the potential of anchor services in Riau Islands Province (Kepri), focusing on service quality and customer relationships that can affect the satisfaction of anchor service users. Data from a survey of 100 vessels using anchor berthing services in Kabil Kepri waters shows that the quality of service and customer relationships significantly affect customer satisfaction. The regression analysis results show that service quality and relationship quality simultaneously contribute significantly to customer satisfaction, with the value of the coefficient of determination reaching 68%. Service quality has a more significant influence than relationship quality on customer satisfaction. The implications of this study show that quality service and good customer relations can increase customer satisfaction when using anchor services. The conclusion of this study emphasises the need for a comprehensive strategy to improve service quality and customer relations in anchorage management in Riau Islands waters. Suggestions for further research are further exploration of more representative indicators of service quality and customer relations and increased academic studies in port marketing, primarily related to anchorage objects.